Pola Asuh Otoritatif dalam Pembentukan Karakter Anak di Keluarga - Travelancya DP, Terza (At- Ta'lim : Jurnal Pendidikan, 2017)
The development of the era demands that humans are not only smart in intellect but also character. Character is formed through character education. The primary and first character education for children is the family environment. In the family environment, the child will learn the basics of behavior that are important to his later life.Character learned by the child through what he sees every day, especially the family members who are around primarily parents.Contoh family behavior directly or indirectly will be studied and imitated by the child. Children imitate parents in the family behave, speak words, express hope, demands, and criticize each other, respond to and solve problems, and express their feelings and emotions.Examples of good behavior will bring good effects for the development of children as well as better. The success of character formation in this child one of them influenced by the example of parents in implementing parenting. Parenting patterns are divided into three types of authoritarian, permissive, and authoritative. Each of these parenting patterns has an impact on child development.Authoritative parenting is the best way to characterize children’s character. Because this authoritative parenting style is characterized by democratic parents, appreciate and understand the state of the child with the advantages of the deficiency so that the child can be a mature, accommodating, and well adjusted self.